A new sesquiterpene from Knema patentinervia - Bakhtiar, M. Taher; Darnis, Deny Susanti; Rezali, Mohd Fazlin (Springer, 2013)
A new widdrane sesquiterpene was isolated from Knema patentinervia by chromatographic methods. The structure was elucidated by spectroscopic methods, including 1H–1H COSY, HMQC, HMBC, and NOESY NMR experiments. The compound showed no inhibition of leukemia cancer cell growth and no inhibition towards bacterial growth of Staphylococcus aureus, Bacillus anthracis, Pseudomonas aeruginosa, and Escherichia coli.